Other causes of intestinal obstruction actino-mycetoma - a case report and literature review - Marín,Jessica Correa (2019)
Abstract Introduction Actinomycosis is a rare infectious disease that affects abdominal organs and simulates oncological disease, hardly ever presents itself as a cause of intestinal obstruction. Symptoms A 43 years old, male patient with two months of left abdominal pain associated to a growth and an 8 kg weight loss, no fever or bowel habit disruption. Interventions A colonoscopy and an abdominal scanography. Results A solid heterogeneous 7 × 3.8 cm mass localized in the splenic flexure of the colon with infiltration of its walls and its surrounding fat. Colon cancer was considered as the first diagnostic possibility. During hospitalization, the patient was taken to an emergency exploratory laparotomy, due to an acute abdominal pain with bowel obstruction symptoms. Histopathological diagnosis Actinomycetoma. Conjoint continuous monitoring with the infectious disease attending, abdominal US and observation did not show new growths. Weight gain and progressive return to daily life was obtained within 8 weeks. Conclusion In low income countries, intestinal actinomycosis should be considered in the differential diagnosis of abdominal masses and chronic inflammatory processes, patient prognosis with proper management is excellent.